Stereological quantification of microvessels using semiautomated evaluation of X-ray microtomography of hepatic vascular corrosion casts - Jiřík, Miroslav; Tonar, Zbyněk; Králíčková, Anna; Eberlová, Lada; Mírka, Hynek; Kochová, Petra; Gregor, Tomáš; Hošek, Petr; Svobodová, Miroslava; Rohan, Eduard; Králíčková, Milena; Liška, Václav (International journal of computer assisted radiology and surgery, 2016)
PURPOSE: Quantitative description of hepatic microvascular bed could contribute to understanding perfusion CT imaging. Micro-CT is a useful method for the visualization and quantification of capillary-passable vascular corrosion casts. Our aim was to develop and validate open-source software for the statistical description of the vascular networks in micro-CT scans. METHODS: Porcine hepatic microvessels were injected with Biodur E20 resin, and the resulting corrosion casts were scanned with 1.9-4.7 [Formula: see text] resolution. The microvascular network was quantified using newly developed QuantAn software both in randomly selected volume probes (n = 10) and in arbitrarily outlined hepatic lobules (n = 4). The volumes, surfaces, lengths, and numbers of microvessel segments were estimated and validated in the same data sets with manual stereological counting. Calculations of tortuosity, radius histograms, length histograms, exports of the skeletonized vascular network into open formats, and an assessment of the degree of their anisotropy were performed. RESULTS: Within hepatic lobules, the microvessels had a volume fraction of 0.13 [Formula: see text] 0.05, surface density of 21.0 [Formula: see text] 2.0 [Formula: see text], length density of 169.0 [Formula: see text] 40.2 [Formula: see text], and numerical density of 588.5 [Formula: see text] 283.1 [Formula: see text]. Sensitivity analysis of the automatic analysis to binary opening, closing, threshold offset, and aggregation radius of branching nodes was performed. CONCLUSION: The software QuantAn and its source code are openly available to researchers working in the field of stochastic geometry of microvessels in micro-CT scans or other three-dimensional imaging methods. The implemented methods comply with reproducible stereological techniques, and they were highly consistent with manual counting. Preliminary morphometrics of the classical hepatic lobules in pig were provided.
Keywords: Microvessels; Corrosion; Python; Stereology; Animals; interpretace obrazu počítačem; mikrocévy; Software; rentgenová mikrotomografie; X-Ray Microtomography; Imaging, Three-Dimensional; software; Swine; zobrazování trojrozměrné; Liver; koroze; Image Interpretation, Computer-Assisted; Pig; zvířata; Porcine; X-ray microtomography; prasata; játra